Mechanical, water resistance and environmental benefits of magnesium oxychloride cement incorporating rice husk ash - Nie, Yanfeng (2023)
Magnesium oxychloride cement (MOC) has received extensive attention as an eco-friendly cement, but its poor water resistance limits its engineering applications. In this study, MOC mixture (MOCM) was modified with 10-50 % rice husk ash (RHA) (wt% of MgO), and the development of their fresh properties, mechanical strength and microstructure was investigated. The results show that the incorporation of RHA to MOCM increases the setting time of the mixture and reduces its flowability. Due to the fine particle size and high reactivity of RHA, the incorporation of an appropriate amount of RHA to MOCM improves the matrix compactness, thereby enhancing the compressive strength of the samples. Although the microstructure of MOCM deteriorates and the strength decreases after immersion in water, the strength retention coefficient of MOCM with 50 % RHA increases by 24.57 % compared with that of plain MOCM. The incorporation of RHA not only reduces the relative content of magnesium oxide in MOCM, but also generates Mg-Cl-Si-H gel, which is beneficial to improve the water resistance of MOCM. Meanwhile, with the increase of RHA content, the carbon emission of MOCM also decreases. Compared with other modification methods, RHA-modified MOCM performs better in terms of water resistance, environmental benefits and strength enhancement.